New curriculum in function of the European concept of quality primary education: Opening space for the autonomy of schools and teachers - Sučević Vlasta; Srdić Vesna (Visoka škola strukovnih studija za vaspitače, Kruševac, 2012)
In the world at large, quality, and its constant improvement, is considered to be the most important phenomenon of our epoch. Here we encounter a new philosophy of living. In terms of education, the time in front of us is characterized by the growing need for knowledge of increasingly good reformative shift of the new curriculum structure brings significant changes, especially in terms of growing understanding of the importance of curricula. The process of curriculum development shifts the emphasis from theoretical modeling to the plan of practice and context - community, school, class, family. The reform shift from classical teaching plans and programes to curricula represents the shift of the core of education process from content to objectives and outcomes of education, and thus the development of the systems of evaluation and self-evaluation in education in addition to basing educational content on educational areas. This paper aims to provide the overview of the new structure of curriculum and its alignment with the European concept of quality education. The main step towards the transition to the outcome-based concept of curriculum involves defining outcomes of education in terms of knowledge, skills, attitudes and values students need to posses after the completion of a certain level of education. The paper considers theoretical concept of the reformative change of curricula and the relation between national and school curriculum, as well as the new structure of school curriculum. The objective of the study is to present a concept of education oriented towards outcomes as well as to opening space for autonomy of schools and teachers.